Identifikasi Talas-Talasan Edible (Araceae) Di Semarang, Jawa Tengah - Sinaga, Khalisa Aini; Murningsih, M; Jumari, J (Bioma : Berkala Ilmiah Biologi, 2017)
Talas-talasan (Family Araceae) is ) is a plant known to the Indonesian people. Araceae has been cultivated and used by Indonesian people. Tuber of Family Araceae have high carbohydrate, carbohydrate composed of amylum (amylose and amylopectin). food quality is determined by ratio of amylose and amylopectin. Information about Araceae in Semarang are still limit. Indonesian people didnâ€™t know potential of the family araceae in field of food. The research objective to determine types ofedible plants from the family Araceae.The research was conducted from April to June 2016. Sampling was conducted at Jabungan, Mluweh and Susukan village, Semarang. Methods of data collection is ekploration. Identification refers to the genera of Araceae (Mayo, 1997) and characterization refers Descriptor Taro (IPGRI, 1999). Based on the results is 13 species of plants from the family Araceae. Differences among species Family Araceae character is the color and shape of the tubers, the tip of leaf blade, the edge of leaf blade, the top and bottom surface of leaf blade, leaf blade holder, and the shape of leaf blade.Â Kata kunci :Identification, Morphology Character, Araceae